THE MEANING OF WOMAN’S INDEPENDENCE IN ECONOMIC BEHAVIOR - Tin Agustina Karnawati (Jurnal Ilmu Komunikasi, 2020)
The woman had double responsibility toward her family, on one side as a mother and the other side they had a productive job to help their family’s economic wealth. This study aimed to describe woman worker in the food home industry in Malang City to view their meaning of woman’s independence in economic behavior. This research used a study case approach with a data collecting method that uses an in-depth interview technique and qualitative analysis model. The study resulted that women workers in their meaning of woman’s independence are: 1) working and provide positive benefits for her and family, 2) support the household economy so hopefully it can improve the family quality of life better, 3) woman’s position in decision making inside the family is determined by their economic contribution in the family, and 4) opportunity to participate in community social activities The economic behavior of women workers in their everyday life, in general, can support their families’ economic well-being. This research could give a contribution in the context of informal education in a family environment, especially instill awareness and understanding as well as realize it in life through attitude, action, and behavior of family members.